77.3k views
0 votes
What is the solution of the equation (x - 5)2 +3(x-5)+9 = 0? Use u substitution and the quadratic formula to solve.​

What is the solution of the equation (x - 5)2 +3(x-5)+9 = 0? Use u substitution and-example-1
User Jazzzzzz
by
5.5k points

1 Answer

6 votes

Answer:

x=
(7+3i√(3) )/(2) and
(7-3i√(3) )/(2)

Explanation:

(x - 5)^(2) +3(x-5)+9

(x - 5)^(2)= x2−10x+25

3(x-5)= 3x-15

x^2-10x+25+3x-15+9

x^2-7x+19=0

a=1 b=-7 c=19

use quadratic formula


\frac{-b+\sqrt{b^(2) -4ac} }{2a}


\frac{-(-7)+\sqrt{-7^(2)-4(1)(19) } }{2}


\frac{7+\sqrt{49{}-4(19) } }{2}


\frac{7+\sqrt{49{}-76 } }{2}


\frac{7+\sqrt{-27{} } }{2}


√(-27) =3i√(3)


(7+3i√(3) )/(2)

User Beld Pro
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.